2000
DOI: 10.1042/0264-6021:3460835
|View full text |Cite
|
Sign up to set email alerts
|

Functional CB1 cannabinoid receptors in human vascular endothelial cells

Abstract: Cannabinoid CB1 receptor mRNA was detected using reverse transcription-polymerase chain reaction (RT-PCR) in endothelial cells from human aorta and hepatic artery and in the ECV304 cell line derived from human umbilical vein endothelial cells. CB1 receptor-binding sites were detected by the high-affinity antagonist radioligand [(125)I]AM-251. In ECV304 cells, both the highly potent synthetic cannabinoid agonist HU-210 and the endogenous ligand anandamide induce activation of mitogen-activated protein (MAP) kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(76 citation statements)
references
References 12 publications
1
72
0
3
Order By: Relevance
“…The CB 1 receptor also modulates ion channels, inducing, for example, inhibition of N-and P/Q-type voltage-sensitive Ca 2+ channels and activation of G-protein-activated inwardly rectifying K + channels [9]. Besides these well-established cannabinoid receptor-coupled signaling events, cannabinoid receptors also modulate several pathways that are more directly involved in the control of cell proliferation and survival, including extracellular signal-regulated kinase (ERK) [12], c-Jun N terminal kinase and p38 mitogen-activated protein kinase [13,14], phosphatidylinositol 3-kinase (PI3K)/Akt [15], focal adhesion kinase [16], and the sphingomyelin cycle [17].…”
Section: Cannabinoids and Their Receptorsmentioning
confidence: 99%
“…The CB 1 receptor also modulates ion channels, inducing, for example, inhibition of N-and P/Q-type voltage-sensitive Ca 2+ channels and activation of G-protein-activated inwardly rectifying K + channels [9]. Besides these well-established cannabinoid receptor-coupled signaling events, cannabinoid receptors also modulate several pathways that are more directly involved in the control of cell proliferation and survival, including extracellular signal-regulated kinase (ERK) [12], c-Jun N terminal kinase and p38 mitogen-activated protein kinase [13,14], phosphatidylinositol 3-kinase (PI3K)/Akt [15], focal adhesion kinase [16], and the sphingomyelin cycle [17].…”
Section: Cannabinoids and Their Receptorsmentioning
confidence: 99%
“…Expression of CB1 has also been demonstrated in rat adipose tissue as well as in primary fat cell cultures (Bensaid et al 2003). At present, the precise function of the CB1 receptor within peripheral tissue is not well understood (Bouaboula et al 1993;Bensaid et al 2003;Cota et al 2003a;Galiegue et al 1995;Liu et al 2000). Studies on the nervous system have elucidated the mechanism of action of the CB1 receptor and made it possible to understand the action of endogenous or exogenous ligands on the physiological functions governed by the central nervous system, in particular the psychotropic effects of cannabis and the regulation of food intake (orexigenic effect of the endocannabinoids) (Cota et al 2003b;Howlett et al 1990;Berry and Mechoulam 2002;Martinez-Gonzalez et al 2004).…”
Section: Introductionmentioning
confidence: 95%
“…For instance, cannabinoid receptors have been determined in human pyramidal cells, T-and B-lymphocytes, keratinocytes, endothelial and epidermal cell lines [17,[27][28][29][30][31], but also in the intestine [32,33] and corneal epithelium [34]. So far, no immunohistochemical study demonstrated the distribution of CB1 and CB2 in human cutaneous nerve fibers.…”
Section: Introductionmentioning
confidence: 99%